1999
DOI: 10.1002/(sici)1521-3889(199911)8:7/9<549::aid-andp549>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Persistent current in normal metals

Abstract: We discuss the recent experiments on persistent current in metallic rings in the backdrop of low temperature decoherence. The observed size of the persistent current, typically on the order of the Thouless energy, e/τD, is much larger than the theoretical results, obtained with or without electron interaction. In considering the phenomenology of both decoherence and persistent current, usually observed in similar systems, we argue towards a dynamic role played by decoherence in the generation of a persistent c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 18 publications
2
20
0
Order By: Relevance
“…However the magnitude of the average persistent current appears to be quite a bit larger (a factor three to five) than what is expected theoretically (Ambegaokar & Eckern 1990a). It has been suggested that this large magnetic response might be related to non-equilibrium effects, such as the coupling to a phonon or photon bath (Mohanty 1999, Kravtsov & Altshuler 2000, Entin-Wohlman et al 2003. In later experiments (Jariwala et al 2001) (see also Reulet et al (1995) and Deblock et al (2002) in this context), a further, and presumably more dramatic, discrepancy is that the sign of the magnetic response -which has not been determined in Lévy et al (1990) -was furthermore not the one expected for a repulsive interaction.…”
Section: Discussionmentioning
confidence: 93%
“…However the magnitude of the average persistent current appears to be quite a bit larger (a factor three to five) than what is expected theoretically (Ambegaokar & Eckern 1990a). It has been suggested that this large magnetic response might be related to non-equilibrium effects, such as the coupling to a phonon or photon bath (Mohanty 1999, Kravtsov & Altshuler 2000, Entin-Wohlman et al 2003. In later experiments (Jariwala et al 2001) (see also Reulet et al (1995) and Deblock et al (2002) in this context), a further, and presumably more dramatic, discrepancy is that the sign of the magnetic response -which has not been determined in Lévy et al (1990) -was furthermore not the one expected for a repulsive interaction.…”
Section: Discussionmentioning
confidence: 93%
“…Recent experiments, however, have challenged this traditional picture. These include the topics of the current paper, saturation of decoherence time at low temperature [10], large persistent current in normal metals [11] and metallic states in two dimensions [12]; it appears that the single-particle picture may be inadequate in explaining these phenomena.…”
Section: Decoherence and The Physics Of Disordered Systemsmentioning
confidence: 99%
“…Normal-metal phase-coherent rings exhibit persistent currents because of electron interference [5,6,11]. The presence of an Aharonov-Bohm flux Φ introduces a phase factor into the boundary condition for the electron wave function,…”
Section: τ φ From Dissipative Persistent Currentmentioning
confidence: 99%
See 2 more Smart Citations